Eastern Cooperative Oncology Group, β2-microglobulin, hemoglobin, and lactate dehydrogenase can predict early grade ≥ 3 infection in patients with newly diagnosed multiple myeloma: A real-world multicenter study - Lu, Xinyi; Liu, Wenhua; Zhang, Lan; Chen, Xinyue; Yang, Liping; Yao, Qiong; Zhao, Jie; He, Shaolong; Wei, Jia; Tian, Weiwei (Frontiers in Microbiology, 2023)
This research explored the clinical application of grade ≥3 infection predictive models for the newly diagnosed multiple myeloma (NDMM) population. It evaluated 306 patients with NDMM based on three different predictive models. The relationship between the grade ≥3 infection rates in NDMM and the scores was analyzed retrospectively. The cumulative incidence of early grade ≥3 infection was estimated using the Kaplan–Meier method and log-rank test to assess the statistical significance of the difference. To compare the predictive performance in the prediction of infection, the ROC curve was used to show the area under the curve (AUC), and DeLong’s test was used to analyze the difference in AUC. The incidence of grade ≥3 infection within the first 4 months of NDMM was 40.20%. Concerning the FIRST score (predictors: ECOG, β2-microglobulin, hemoglobin, and lactate dehydrogenase), GEM-PETHEMA score (predictors: albumin, male sex, ECOG, and non-IgA type MM), and IRMM score (predictors: ECOG, serum β2-microglobulin, globulin, and hemoglobin), the probability of early grade ≥3 infection in the different groups showed statistically significant differences (low-risk vs. high-risk: 25.81% vs. 50.00%, P<0.001; low-risk vs. moderate-risk vs. high-risk: 35.93% vs. 41.28% vs. 60.00%, P=0.045; low-risk vs. moderate-risk vs. high-risk: 20.00% vs. 43.75% vs. 52.04%, P<0.001). Statistical differences existed in the probability of early grade ≥3 infection among the different groups by the FIRST and IRMM scores but no statistical differences in the GEM-PETHEMA score (P<0.001, P<0.001, and P=0.090, respectively). The FIRST score showed good discrimination and simple calculation with highest AUC. Further subgroup analysis showed that the FIRST score could still apply for patients treated with bortezomib-based regimen and frail patients. Our findings indicate that the FIRST score (consisting of ECOG, β2-microglobulin, hemoglobin, and lactate dehydrogenase) is a simple and robust infection stratification tool for patients with NDMM and could be used in routine clinical work.